PENGARUH NILAI TUKAR, SUKU BUNGA, DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Saputra, Apen (KHOZANA: Journal of Islamic Economic and Banking, 2019)
Abstract This study aims to identify the effect of exchange rate, interest rate and inflation rateoncomposite stock price indexat Indonesia stock exchange. Design used in this research is associative design. There are four variables. Those are independent variables which exchange rate, interest rate and inflation rate, and dependent variables is composite stock price index. The samples used in this research are data on january 2011 until december 2015. The analytical toolusedis multiple linear regression. According to the research result, find: (1) There is a significant effect exchange rate, interest rate, and inflation rate to composite stock price index at Indonesia Stock Exchange, (2) There is a negative  and significant effect exchange rate on composite stock price index in Indonesia Stock Exchange, (3) There is no significant effect interest rate on composite stock price index in Indonesia Stock Exchange, and (4) There is no significant effect inflation rate on composite stock price index in Indonesia Stock Exchange.   Keywords: Exchange Rate, Interest Rate, Inflation Rate, and Composite Stock Price Index